Practices of fish farmers: techniques, characteristics, feeding, and type of aquaculture farming in the district of Antsirabe I Vakinankaratra Madagascar - Rindra, Rabarison; Nicole, Ramanambe Ravelomanantsoa; Tahina, Rabeharitsara Andry; Ngbolua, Koto-te-Nyiwa (Budapest International Research and Critics University, 2024)
This study aims to explore the current practices of fish farmers, focusing on the different rearing techniques and the use of aquaculture environments in Antsirabe Vakinankaratra. In particular, the survey examines the management of rearing environments, the selection of species for rearing types, feeding and the characteristics of rearing environments. Many fish farmers notice significant benefits from their farming method. However, several problems persist, this situation, calls for training initiatives and financial support to optimize their production and ensure the sustainability of their activities.